UJI AKTIVITAS ANTIDEPRESAN PERASAN RIMPANG TEMULAWAK (Curcuma xanthorrhiza, Roxb) TERHADAP MENCIT PUTIH JANTAN (Mus musculus) - Dian Kartikasari; Hairunisa Hairunisa; Emy Nadya Natasha (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACTPrevention and treatment with synthetic antidepressants has many side effects that affect the central nervous system and usage must be under the supervision of a doctor. Whereas prevention and traditional medicine relatively do not cause side effects, are inexpensive, and easy to obtain. One example of traditional medicine from natural ingredients, which can provide an antidepressant effect is ginger rhizome. This research aims to determine whether ginger rhizome have antidepressant effects on male white mice. Antidepressant effect testing was carried out on male white mice (Mus musculus) using the forced swim test method. The part of the plant used is the rhizome of the ginger plant. Curcuma rhizome is made with juice and given orally with a concentration of 20%, 40%, and 60%. The negative control used is Na CMC 0.5%, while the positive control used, namely amitriptilyn. The parameters observed were the duration of immobility time, swimming time and climibing time (in seconds) which were calculated from minutes 3-6 for 6 minutes, and statistical tests were carried out with a confidence level of 95%. The results showed that at a concentration of 40% the curcuma rhizome juice had a significant value (p> 0.05) which means that there was no significant difference in antidepressant effect (%) from the juice of temulawak 56.31% and amitriptylin 78.78%Keywords: ginger rhizome, antidepressants, the forced swim test